2020
DOI: 10.1038/s41418-020-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Squamous differentiation requires G2/mitosis slippage to avoid apoptosis

Abstract: The cellular mechanisms controlling cell fate in self-renewal tissues remain unclear. Cell cycle failure often leads to an apoptosis anti-oncogenic response. We have inactivated Cdk1 or Polo-like-1 kinases, essential targets of the mitotic checkpoints, in the epithelia of skin and oral mucosa. Here, we show that inactivation of the mitotic kinases leading to polyploidy in vivo, produces a fully differentiated epithelium. Cells within the basal layer aberrantly differentiate and contain large or various nuclei.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Keratinocytes are resistant to apoptosis unless they undergo Sunburn (Bell and Megeney, 2017;Sanz-Gómez et al, 2020a). Consistently, no apoptotic sub-G1 cells were detected in the stratifying cultures (Fig.…”
Section: Primary Keratinocytes Undergo Dna Damage During Proliferationsupporting
confidence: 69%
See 1 more Smart Citation
“…Keratinocytes are resistant to apoptosis unless they undergo Sunburn (Bell and Megeney, 2017;Sanz-Gómez et al, 2020a). Consistently, no apoptotic sub-G1 cells were detected in the stratifying cultures (Fig.…”
Section: Primary Keratinocytes Undergo Dna Damage During Proliferationsupporting
confidence: 69%
“…Interestingly, we found that mushroom cells accumulate mitotic markers such as cyclin A or cyclin B (Zanet et al, 2010), further suggesting a natural link between mitosis arrest and differentiation. It is also noteworthy that lack of essential mitotic kinases Aurora B kinase or Polo-like kinase 1 in vivo produces a fully differentiated squamous epithelia (Sanz-Gómez et al, 2020a). The frequent presence of 53BP1 NBs in differentiating cells in vitro and in situ supports the notion that irreparable damage leads to differentiation.…”
Section: Discussionmentioning
confidence: 82%
“…Pathway analysis of CDC20 interacting proteins suggested additional roles of CDC20 outside cell cycle regulation, with a significant enrichment of specific cellular processes, including protein modification, localization and degradation, telomeres regulation, transcription, and other signaling pathways, as Hippo, TGF-β, β-catenin, MAPK (Table S 1 ). Accordingly, it has been recently shown that CDC20 exerts a pivotal role in different cell type-specific biological processes, as ciliary disassembly [ 87 , 88 ], brain development [ 89 , 90 ], necrosis suppression in neural stem cells under catastrophic cellular stresses [ 91 ], tissue homeostasis and cell fate in human keratinocytes [ 92 , 93 ], genomic stability [ 94 , 95 ], aging [ 96 ] and autophagy [ 97 , 98 ] (Fig. 3 A-D).…”
Section: Main Textmentioning
confidence: 99%
“…If the danger is not mitigated, permanent growth arrest assures that cells containing a mutated genome do not propagate. Additionally, differentiation was recently identified as a mechanism by which polyploidy epithelial cells are prevented from growth [ 78 ]. Despite the benefits to the cell, pauses to cellular growth run counter to the requirements for β-HPV replication.…”
Section: Resultsmentioning
confidence: 99%